Clinical case of a 44-year-old patient with newly diagnosed peripheral T-cell lymphoma unspecified (Lennert’s lymphoma) and Loeffler’s endocarditis - Yu. E. Ryabukhina; O. L. Timofeeva; A. A. Akhobekov; P. A. Zeynalova; F. M. Abbasbeyli; G. F. Allakhverdieva; A. G. Zhukov; V. V. Fedotov; L. A. Shestakova (Онкогематология, 2023)
Peripheral T-cell lymphoma unspecified (PTCLu) in most cases has an aggressive clinical course and is characterized by a high frequency of extranodal lesions. One of the manifestations of PTCLu, in particular Lennert’s lymphoma, is eosinophilia. Regardless of the development mechanism, eosinophilia can be accompanied by heart damage, leading to endomyocardial fibrosis, ventricular thrombosis and, in the final stage, to restrictive cardiomyopathies, which are manifestations of Loeffler’s endocarditis (LE). The presence of LE aggravates the course and prognosis of PTCLu, primarily limiting the possibilities of antitumor drug therapy. A multidisciplinary approach to managing a patient with PTCLu and concomitant LE makes it possible to diagnose and start both specific and cardiotropic therapy in a timely manner, ultimately improving the prognosis. A clinical case of a 44‑year-old patient with newly diagnosed PTCLu (Lennert’s lymphoma) and LE is presented.